Enzymes involved in the anaerobic oxidation of n-alkanes: from methane to long-chain paraffins - Callaghan, Amy V. (Frontiers in Microbiology, 2013)
Anaerobic microorganisms play key roles in the biogeochemical cycling of methane and non-methane alkanes. To date, there appear to be at least three proposed mechanisms of anaerobic methane oxidation (AOM). The first pathway is mediated by consortia of archaeal anaerobic methane oxidizers and sulfate-reducing bacteria via ‘reverse methanogenesis’ and is catalyzed by a homologue of methyl-coenzyme M reductase. The second pathway is also mediated by anaerobic methane oxidizers and sulfate-reducing bacteria, wherein the archaeal members catalyze both methane oxidation and sulfate reduction and zero-valent sulfur is a key intermediate. The third AOM mechanism is a nitrite-dependent, “intra-aerobic” pathway described for the denitrifying bacterium, ‘Candidatus Methylomirabilis oxyfera.’ It is hypothesized that AOM proceeds via reduction of nitrite to nitric oxide, followed by the conversion of two nitric oxide molecules to dinitrogen and molecular oxygen. The latter can be used to functionalize the methane via a particulate methane monooxygenase. With respect to non-methane alkanes, there also appears to be novel mechanisms of activation. The most well-described pathway is the addition of non-methane alkanes across the double bond of fumarate to form alkyl-substituted succinates via the putative glycyl radical enzyme, alkylsuccinate synthase (also known as methylalkylsuccinate synthase). Other proposed mechanisms include anaerobic hydroxylation via ethylbenzene dehydrogenase-like enzymes and an ‘intra-aerobic’ denitrification pathway similar to that described for ‘M. oxyfera.’